2011
DOI: 10.1007/s00417-011-1773-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intravitreal bevacizumab (Avastin) on the porcine retina

Abstract: A single intravitreal injection of bevacizumab does not result in structural changes of the porcine retina, nor in induction of gliosis or apoptosis. The bevacizumab-induced transcriptional downregulation of VEGF and upregulation of Kir4.1 might protect the retina from the development of vascular and cytotoxic edema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 37 publications
0
4
0
3
Order By: Relevance
“…In fact, while Lassota et al 2,40 found less fluorescein leakage of surgically induced CNV treated with bevacizumab, the lesion sizes were no different from controls. Iandiev et al 41 studied the effect of bevacizumab in the live pig model and measured a decrease in the transcriptional expression of VEGF-A. However, their model did not include induction of CNV.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, while Lassota et al 2,40 found less fluorescein leakage of surgically induced CNV treated with bevacizumab, the lesion sizes were no different from controls. Iandiev et al 41 studied the effect of bevacizumab in the live pig model and measured a decrease in the transcriptional expression of VEGF-A. However, their model did not include induction of CNV.…”
Section: Discussionmentioning
confidence: 99%
“…14, 40 Guo et al 14 evaluated the effect of bevacizumab on cultured rat retinal Müller glial cells as well as in vivo in adult rats injected intravitreously. The authors concluded that bevacizumab exerts no inhibition of rat retinal Müller glial cells.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that bevacizumab exerts no inhibition of rat retinal Müller glial cells. Iandiev et al 40 evaluated the effect of bevacizumab on the retina of adult pigs and concluded that a single intravitreal injection of bevacizumab does not induce gliosis. However, both studies evaluated retinal glial cells of adult animals and their findings cannot be extrapolated to the developing retina.…”
Section: Discussionmentioning
confidence: 99%
“…Yu e col., 2008, afirmaram que é pouco provável que a imunoneutralização específica do VEGF seja realizada pelo BVZ em murinos (107). No entanto, estudos em camundongos (8,13,21,23,(108)(109)(110) , em porcos (48) e em coelhos (111) responderam ao tratamento com BVZ, tanto em animais adultos quanto em prematuros.…”
Section: Discussionunclassified
“…A apoptose é amplamente estudada por grupos que avaliam a segurança e toxicidade do BVZ na retina, seja por estudos de fragmentação de DNA (TUNEL) ou pela expressão gênica e imunomarcação das caspase-3 e caspase-9 (36,(46)(47)(48)(49)(50)(51) . Estes estudos reforçam o papel neuroprotetor do VEGF no ambiente retiniano, que estimula a produção de BCL-2, proteína anti-apoptótica (52)(53)(54)(55) .…”
Section: O Bvz E Sua Influência Na Apoptose E Autofagiaunclassified